2016
DOI: 10.1111/1750-3841.13302
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Constituents of Hainan Morinda citrifolia (Noni) Leaves

Abstract: Noni (Morinda citrifolia L.) is an edible and medicinal plant distributed in Hainan, China. The antibacterial activities of the extracts of water (WE), petroleum ether (PEE), ethyl acetate (EAE), chloroform (CE), and n-butanol (BE) were assayed by the disk diffusion method. The results showed that the extracts from Noni leaves possessed antibacterial effects against Bacillus subtilis, Escherichia coli, Proteus vulgaris, and Staphylococcus aureus. Among 5 different extracts, the BE produced the best antibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…Anthraquinone class compounds can also be found in poorly exploited M. citrifolia structures. Wang et al (2016) isolated two new anthraquinones previously unknown from the bark of the M. citrifolia stem: 1,3-dihydroxy-5-methoxy-6-methoxymethyl-2methyl-9,10-anthraquinone and 1,3-dihydroxy-5-methoxy-2,6bismethoxymethyl-9,10-anthraquinone. In addition to those already mentioned, another 10 known derivatives of anthraquinones were identified, among them damnacantal and three more coumarin derivatives, including scopoletin.…”
Section: Biochemical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthraquinone class compounds can also be found in poorly exploited M. citrifolia structures. Wang et al (2016) isolated two new anthraquinones previously unknown from the bark of the M. citrifolia stem: 1,3-dihydroxy-5-methoxy-6-methoxymethyl-2methyl-9,10-anthraquinone and 1,3-dihydroxy-5-methoxy-2,6bismethoxymethyl-9,10-anthraquinone. In addition to those already mentioned, another 10 known derivatives of anthraquinones were identified, among them damnacantal and three more coumarin derivatives, including scopoletin.…”
Section: Biochemical Characteristicsmentioning
confidence: 99%
“…Recently, Wang et al (2016) extracted two new anthraquinones from the barks of the M. citrifolia stem: 1,3-dihydroxy-5-methoxy-6-methoxymethyl-2-methyl-9,10-anthraquinone (1) 3-dihydroxy-5-methoxy-2,6-bismethoxymethyl-9,10-anthraquinone (2). Nuclear magnetic resonance spectroscopy assay (NMR spectroscopy) revealed that both compounds have a very similar molecular skeleton.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Growing evidence suggests that noni has important antimicrobial and antibacterial activities. Extracts of noni leaves made with three different solvents, ethyl acetate extract, n -butanol, or water, showed a very strong antimicrobial and antibacterial activity against some microorganisms, including Proteus vulgaris , Staphylococcus aureus , Bacillus subtilis , and Escherichia coli [17]. …”
Section: Morinda Citrifolia Linn (Noni)mentioning
confidence: 99%
“…It has been investigated as an alternative in anticancer, antibacterial, and antimicrobial therapies, and in the treatment of esophageal reflux and ulcers in animals [17,18,19,20,21]. In humans, there are few studies showing the beneficial effects of noni.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the polarity order of organic solvents, petroleum ether, ethyl acetate, chloroform and n butanol were added in succession to extract the crude extract of E. dulcis peel [28,29]. Each extraction was repeated three times to obtain four organic solvent extracts.…”
Section: Extraction and Separation Of Compounds Present In E Dulcis mentioning
confidence: 99%